UNIPLEX AND DUPLEX RT-PCR PROTOCOLS FOR DETECTION OF PVY AND PLRV IN APHIDS FROM POTATO FIELDS - Venkateswarlu, V; Sridhar, J; R, Baswaraj; A, Jeevalatha; Malik, Kamlesh; Bhatnagar, Anuj; Kumari, Neelam; Sharma, Sanjeev; Nagesh, M; Singh, B P; Chakrabarti, S K (Potato Journal, 2017)
Myzus persicae is the principal vector of economically important potato viruses, especially Potato virus Y and Potato leaf roll virus. Uniplex and duplex reverse transcription polymerase chain reaction (RT-PCR) assays were standardized and validated to detect PVY and PLRV in field collected populations of M. persicae using primers specific to coat protein. Results revealed that an annealing temperature of 62Â°C was found optimum for amplification of both viruses. Uniplex assay developed in this study could detect PVY in M. persicae samples of Modipuram, Jalandhar, Solan, Patna and Shillong. Duplex assay could successfully detect both viruses in M. persicae samples of Kodaikanal and Shillong. PCR products ofPVY and PLRV were direct sequenced and got desired nucleotides of 380 and 492 bp, respectively which further confirmed the robustness of the protocols. Therefore, these protocols could be helpful to detect PVY and PLRV in M. persicae for healthy potato seed production.